The Relationship between ESG (Environmental, Social, Governance) Principles and the Fulfillment of the Right to Work for Persons with Disabilities - Ni Nyoman Mitha Sakarani; I Gede Agus Kurniawan (Faculty of Law, Universitas Pekalongan, 2025)
The principle of Environmental, Social, and Governance (ESG) has become one of the key benchmarks in sustainable business practices, including in Indonesia. However, the implementation of this principle is often understood primarily within the context of environmental and governance dimensions, while the social dimension—particularly the fulfillment of the right to work for persons with disabilities—remains insufficiently addressed. This situation underscores the need for an in-depth study of how ESG principles can be integrated into Indonesian business law to strengthen the protection of disability labor rights. This research aims to analyze the relationship between ESG principles and the fulfillment of the right to work for persons with disabilities, as well as to examine the extent to which Indonesian business law supports such integration. The study employs normative legal research with a statute approach and a conceptual approach. Primary legal materials include Law No. 8 of 2016 on Persons with Disabilities, the Manpower Law, and sustainability regulations such as OJK Regulation No. 51/2017. The findings reveal that Indonesian business law provides a normative foundation for disability labor inclusion through mandatory recruitment quotas, obligations to provide disability-friendly workplace facilities, and sustainability reporting requirements. The novelty of this research lies in its integrative analysis that links ESG principles with business law instruments, thereby offering a new perspective in viewing ESG not merely as a voluntary practice but also as a legal obligation that supports social sustainability. These findings contribute to the development of business law literature while also providing recommendations to enhance inclusive labor practices in Indonesia